Malaria Active Case Finding is a Necessary Strategy in the Malaria Elimination Program: A Successful Experience in Iran - Maryam Sarani; Gholamali Javdan; Amin Ghanbarnejad; Ebrahim Eftekhar; Reza Safari; Khojasteh Sharifi- Sarasiabi; Shaghayegh Khojasteh; Habibollah Turki (Shiraz University of Medical Sciences, 2023)
Background: Case finding and malaria foci management is significant strategy for the prosperous performance of amalaria elimination program. Therefore, detection, treatment. and follow-up of all cases (symptomatic & Asymptomatic) in malaria elimination program is necessary. This study aimed to find an active cases of malaria in Bashagard (With a previous history of local malaria transmission) with emphasis on the use of molecular methods in order to successfully implement the malaria elimination program.Methods: A cross-sectional study was conducted to examine more precise the positive cases reported and to identify possible cases of additional malaria. In the first stage, all eligible residents of the community were sampled. In the next step, the villagers who had moved to work in the neighboring city were identified and sampled. In this study, 230 people participated to be tested for malaria by microscopic, Rapid Diagnostic Tests and Nested- PCR techniques.Results: In the first phase of the study, three positive cases of Plasmodium vivax were reported using microscopic and RDT methods. In the second step of the survey, an asymptomatic malaria reservoir was identified using molecular technique.Conclusion: The results of this study emphasize the important role of active cases finding using molecular techniques along with routine diagnostic methods in malaria control and elimination programs.